Begravet og oprejst - Petersen, Anders Klostergaard (Religionsvidenskabeligt Tidsskrift, 1995)
The purpose of the article is to present a ritual-theoretic reading of an important Pauline baptismal text thereby gaining not only a deeper understanding of the Pauline baptismal references but also a more profound knowledge of the Pauline theology in toto. On the basis of van Gennep's essential work "The Rites of Passage", a heuristic definition of initiation is developed and applied to Romans 6:1-14.